Very short-term heat acclimation: are 3 exercise sessions in the heat enough to partially reduce heat-induced performance decrements? - Callovini, A.; Fornasiero, A.; Savoldelli, A.; Stella, F.; Bortolan, L.; Pellegrini, B.; Schena, F. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Introduction: Many sporting events are held every year in hot environments, with temperatures upwards of 35°C and above 50% of relative humidity. In order to limit heatinduced performance decrements (ranging from 6 to 16% in trained athletes)1, heat acclimatization/acclimation (HA) protocols have been proposed. Although complete physiological adaptation to hot environments may require up to 14 days to occur, cardiovascular and perceptual adaptations have been noticed even after only 3 days of heat exposures. Despite being short-term acclimations protocols of interest to elite athletes, in order to limit costs and modifications of training programs, the expected performance enhancements, as well as the physiological adaptation induced by this kind of programs are not completely understood. In this study, we investigated the effects of a 3-day very short-term heat acclimation protocol (VSTAP) on performance, physiological and perceptual responses to exercise in the heat. Methods: 6 well trained male cyclists (age: 30.9±8; weight: 75.5±7) performed a preliminary normothermic (18°C- 50% RH) maximal cardiopulmonary exercise test (CPET) in order to define individual Peak Power Output (PPO). CPET was followed by normothermic and a hot (35°C-50% RH) Time to Exhaustion tests (nTTE vs hTTE, interspersed by at least 48-72 hours) with a relative intensity set at 75% of PPO. Performance tests were repeated after the VSTAP, consisting of 3 days- 1,5 hours training at 50% of PPO. During TTE tests, final performance time, blood lactate [La], maximal and mean Heart Rate (HR), Rate of Perceived Exertion (RPE), Thermal Sensation (TS) and Ear Temperature (Et) were evaluated. Moreover, we monitored HR, TS, RPE and Et throughout the training sessions (1,2,3). All data from TTE and training sessions were analyzed using ANOVA for repeated measures. Results: TTE performance increased at POST both in H (+38%) and N (14%) (general condition effect p<0.05). A similar general condition effect (p<0.05) was reported for TSend, that decreased at POST in both conditions. Maximal RPE and HR were similar in N and H both at PRE and POST. No effect of time was reported on Et, which was higher in H. [La] decreased at POST in N. Both mean Et and HR decreased during training 3 compared to training 1 (p<0.05) ( -0.4 °C and -6% during training 3, respectively). Conclusion: Considering preliminary data, a VSTAP seems to induce performance improvements in both normothermic and hot conditions. This could be related to improved thermoregulation processes (partially seen in decreased mean Et at training 3) and some cardiovascular adaptations (decrease in HR). This is probably due to an increase in plasma volume and consequently increased CO with a contemporary reduction in sympathetic nervous system activity. Improvements also in nTTE need further investigations to ensure the effect of heat training on temperate performance.